What Helped Me Innovate: Identified Motivation Factors from Canadian Innovators’ Education Experiences - Soleas, Eleftherios; Bolden, Ben (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
Past innovation research has focused on business contexts and prodigy, leaving the insights of today’s successful innovators in a range of fields overlooked in their utility to inform the education of our next generation of innovators. This mixed method study combined surveys (n = 500) and interviews (n = 30) of Canadian innovators to identify motivation factors that could be leveraged in formal and informal education to make innovation more likely in Canada. The findings point to methods of maximizing expectancies and values, while proactively mitigating the costs of innovating. Recommendations are made for teachers, mentors, and decision makers for better stoking the capacity to innovate through education. Keywords: innovation, innovators, maximizing innovative capacity